2021
DOI: 10.1108/joepp-06-2020-0104
|View full text |Cite
|
Sign up to set email alerts
|

Changes in workplace practices during the COVID-19 pandemic: the roles of emotion, psychological safety and organisation support

Abstract: PurposeThe purpose of the study is to investigate the psychological safety, organisation support and emotion in the workplace during the transition from office to home working during the COVID-19 pandemic crisis. Past studies on emotion in the workplace mostly focus on types of discreet emotion, in relation to positive and negative emotions (e.g. Connelly and Torrence, 2018; Rubino et al., 2013). Other studies reported that emotions are derived from social comparison processes (Matta and Dyne, 2020). During a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(179 citation statements)
references
References 101 publications
(146 reference statements)
9
158
0
12
Order By: Relevance
“…A good understanding of which physical, emotional and behavioral symptoms of health problems do employees face during the COVID-19 epidemic could improve better health, well-being, productivity and satisfaction among employees during the COVID-19 and also after the COVID-19. According to Lee (2021), Agus and Selvaraj (2020), Srivastava and Agarwal (2020), Zhang et al (2020), Shareena and Mahammad (2020) and Hayes and Curran (2020), there is more need for suitable human resource management during the COVID-19 epidemic and suitable working environment for employees during the COVID-19 epidemic and also after the COVID-19 epidemic. Moreover, Stein (2020), Gavidia ( 2020 The study findings show that physical, emotional and behavioral symptoms of health problems among employees during the COVID-19 epidemic are more strongly expressed as before the COVID-19 epidemic, and also the study findings show that there are significant differences regarding physical, emotional, and behavioral symptoms of health problems among employees who worked from home and those who worked at the workplace during the COVID-19 epidemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good understanding of which physical, emotional and behavioral symptoms of health problems do employees face during the COVID-19 epidemic could improve better health, well-being, productivity and satisfaction among employees during the COVID-19 and also after the COVID-19. According to Lee (2021), Agus and Selvaraj (2020), Srivastava and Agarwal (2020), Zhang et al (2020), Shareena and Mahammad (2020) and Hayes and Curran (2020), there is more need for suitable human resource management during the COVID-19 epidemic and suitable working environment for employees during the COVID-19 epidemic and also after the COVID-19 epidemic. Moreover, Stein (2020), Gavidia ( 2020 The study findings show that physical, emotional and behavioral symptoms of health problems among employees during the COVID-19 epidemic are more strongly expressed as before the COVID-19 epidemic, and also the study findings show that there are significant differences regarding physical, emotional, and behavioral symptoms of health problems among employees who worked from home and those who worked at the workplace during the COVID-19 epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Whether on a collective or individual level, there has naturally been pressure put on these relationships as the business environment and our ways of working have rapidly adapted in response to COVID-19 (Eaton and Heckscher, 2021). Fostering positive employee relations during the COVID-19 leads to beneficial business outcomes and contributes to employees' well-being (Lee, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…26 Support for HCW mental health may be facilitated by organisational support and may underpin the psychological safety needed to nimbly respond to disasters. 27 Rounding out the need for mental health support, recent reviews have identified frontline and non-physician HCWs as having the greatest mental health needs of HCWs during the COVID-19 pandemic. 24 As COVID-19 persists and other pandemics emerge, the role of employee occupational health providers in national healthcare systems should not be undervalued.…”
Section: Discussionmentioning
confidence: 99%
“…It still could not dissolve this problem or issue when most of this work from home arrangement can take a long period of time in the world of work. It can only get a positive outcome if there is organizational support that endorses digitalization in the companies for remote working (Lee, 2021). Furthermore, being away from workers and employees also resulted in the lack of ad-hoc discussion which some may see as an importance to ensure proper planning and follow-up (Waizenegger et.…”
Section: Methodsmentioning
confidence: 99%